Environmental enrichment effects on the reproductive behavior of captive nurse sharks Ginglymostoma cirratum - Colbachini, Helen [UNESP]; Pizzutto, Cristiane Schilbach; Souza Mesquita, Leonardo Mendes de [UNESP]; Gadig, Otto Bismarck Fazzano [UNESP] (Springer, 2021)
Nurse sharks (Ginglymostoma cirratum, Ginglymostomatidae) are one of the most exhibited shark species in aquariums worldwide. However, in these locations, their reproductive success rate is frequently low. Considering that there is probably an olfactory mediation for nurse shark reproduction, and that environmental enrichment has a potentially positive effect on reproduction of captive animals, the present study aimed to evaluate whether the use of olfactory enrichment would stimulate olfactory-driven behaviors and consequently generate effects in the exhibition of reproductive behaviors by the species both in the short and long term. The study was divided into three phases (control, short-term enrichment and long-term enrichment), was conducted at two institutions with distinct husbandry and used aqueous extracts of basil leaves as olfactory enrichment. Eleven individuals were selected through focal sampling for behavioral observations with instantaneous recording, the total of 120 h of observation were divided into active and inactive periods. Results showed that basil-based olfactory enrichment was effective in increasing the occurrence of reproductive behaviors in both female and male nurse sharks. Additionally, the long-term results showed higher effects in males, which strengthen the theory of olfactory mediation of reproductive behavior in the species as individuals became aware of the sensory cues in the environment and performed more olfactory-driven reproductive behaviors. It is important to note that enrichment effects are different between sexes and therefore close monitoring and scheduling are essential to avoid over-stimulation or habituation to the enrichment.
Keywords: Captive breeding; Olfactory enrichment; Olfactory mediation; Shark reproduction